Early Implementation of the Koperasi Desa Merah Putih Program: A Qualitative Case Study in Pulai Payung Village, Mukomuko Regency - Grache Viola; Titi Darmi (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This study examines the early implementation of the Koperasi Desa Merah Putih Program in Pulai Payung Village, Mukomuko Regency, focusing on the transition from formal establishment to operational performance. A qualitative single-case study used semi-structured interviews, observation, and document analysis. Informants were purposively selected from local government officials, village authorities, cooperative managers, registered members, and residents with direct knowledge of program implementation. Data were analyzed using Miles, Huberman, and Saldaña’s interactive model and interpreted through the input, process, output, outcome, and impact dimensions. The findings show that the cooperative has obtained legal status, a Business Identification Number, and a Taxpayer Identification Number, but managerial competence, capital, business-unit development, and active member participation remain limited. Initial outcomes include improved institutional coordination, emerging collective economic initiatives, and gradual trust building. However, the program has not yet produced demonstrable impacts on household income, employment, price stabilization, or village economic transformation because implementation remains at an early stage. The study identifies an implementation gap between administrative compliance and substantive community benefits, indicating the need for sustained mentoring, transparent governance, member activation, and impact-oriented monitoring.